COMPARATIVE STUDY OF EFFICACY OF E FAST WITH CT CHEST IN CHEST TRAUMA PATIENTS - S, VIDHYAALAKSHMI; P.B, SUDARSHAN (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
INTRODUCTION: Blunt chest trauma presents a significant challenge in the emergency setting, often requiring rapid and accurate diagnostic assessment to guide management. This prospective study aimed to evaluate the diagnostic efficacy of E-FAST (extended Focused Assessment with Sonography in Trauma) compared to CT chest in blunt chest trauma patients and also clinical correlation with imaging findings. METHODS: Retrospective observational study conducted saveetha medical college in during the period of November 2022 to march 2024. The inclusion criteria were: all blunt trauma patients and incidental findings in other associated injuries . exclusion criteria included age less than 18 years and associated with other injuries only .Various parameters considered were based on the history, clinical signs ,radiological findings , vitals and alive or death . The software used for statistical purposes were IBM SPSS software . RESULTS: Total of 100 patients were reported to the trauma centre during the period of the study. The male-to-female ratio was 7:1 .14% E fast negative, but CT chest positive , 38% signs and symptoms related to chest, 24% EFAST negative but haemothorax and pneumothorax seen ; vitals were stable in 87% of the patients ; 28% no associated injuries , death was found to be in the age groups mostly involving the >60 and < 20 years , involving only 3 % of the people . CONCLUSION: E Fast and CT CHEST can be used to as a triaging tool in blunt chest trauma . Even though E FAST cannot detect positive findings in chest trauma patients, number is very negligible , Thus can be concluded that E FAST can be used as an effective tool in diagnosing chest trauma patients . Thus there is no significant difference between NCCT CHEST and EFAST in the evaluation of chest trauma patients affirming the utility of both in the clinical practice .